Bulgaria - Investment Climate Assessment : Volume 3. Technical Appendices - World Bank (Washington, DC, 2012)
Sustained improvements in living standards depend on broad-based economic growth. This will only take place when firms improve worker productivity by investing in human and physical capital and increasing their technological capacity. But firms will only invest when the investment climate is favorable. The goal of the Bulgaria Investment Climate Assessment (ICA) is to evaluate the investment climate in all its operational dimensions and to promote policies to strengthen the private sector. The ICA is largely based on results from the World Bank Enterprise Survey. The 1,000-firm survey was conducted in late 2007 and collects detailed information on firm performance, what managers see as the main obstacles that they face, and objective data on various aspects of the investment climate. Additional sources of information are used to supplement the survey data, including the World Bank's Doing Business Report, a study that provides detailed, comparable data on regulation across the world, data from the National Statistical Institute, and reports from the Government of Bulgaria, the World Bank, the International Monetary Fund, the European Union, academics, and other sources.